Parametric Investigation of the Urban Heat Island Using the Internet of Things (IoT) in Putrajaya, Malaysia - Zambri Harun; Altaf Hossain Molla; Hashimah Hashim; Muhamad Zameri Mat Saman; Eslam R. Lotfy (International Journal of Integrated Engineering, 2024)
The urban heat island (UHI) phenomenon has become a critical issue for Putrajaya, the administrative capital of Malaysia. This research experimentally investigates the UHI phenomenon in Putrajaya using the Internet of Things (IoT) and assesses the urban heat island intensity (UHII). This study investigates the effect of wind speed and rainfall on UHII. This study has chosen two strategic locations for green zone reference and residential or commercial zone reference, respectively. The major equipment used here are 81000 ultrasonic anemometer by R.M. Young for temperature and an IoT system fabricated and maintained by Enomatrix. We have installed an IoT-enabled system embedded with different sensors and equipment to record, store and analyze the data from selected strategic locations. The results of this study indicate the presence of UHI in this city and reveal that the maximum UHII is approximately 3.6 °C. Furthermore, the parametric analysis reveals that wind speed has a significant influence on UHII. Moreover, this research shows that rainfall has great potential to reduce the UHII. The findings of this study provide valuable insights into the UHI effect in Putrajaya and can be used to inform urban planning and design decisions to mitigate the UHI effect. The use of IoT and parametric analysis in this study also demonstrates the potential of these technologies to improve our understanding of urban environments and inform sustainable urban development.